The impact of rail passenger transport, as a component leading to the increase of the security and movement of people, on traffic security in terms of the Covid-19 pandemic - Paweł Krystian Lubiewski; Bartosz Kozicki; Łukasz Foryś; Bogusław Kogut (Journal of Modern Science)
Objectives The aim of the article is to demonstrate the impact of passenger rail transport on road traffic security, taking into account the Covid-19 pandemic.